Jeremy Belknap and the Origins of American Exceptionalism - Agnès Delahaye (Transatlantica)
This paper analyses the commercial and institutional context in which Jeremy Belknap founded the Massachusetts Historical Society in 1791-1792. It reads his “Four Dissertations” of 1792 as a series of methodological and theoretical arguments in favor of the unique chronology and thematic content of American history. It argues that Belknap’s overall historical project is the origin of American exceptionalism as a historical practice, based on an exclusive focus on settlement and expansion as the engines of history, and on the experiences of American settlers since their arrival on the continent, as the only sources on which to build a relevant paradigm of the American character. His legacy is problematic, but it represents a crucial avenue of postcolonial inquiry, in which the structuring effects of exceptionalist historiography can be studied.